EQviz: A visualization tool for monitoring world earthquakes - Nitchanan Prapaitrakul (2018)
Copyright 2015 © ACM. This paper presents EQviz, a visualization tool for monitoring earthquakes with the magnitude of 6.0 or larger that take place around the world from 2000 to 2015. EQviz provides four modes of display: instant, aggregate, analysis, and selected area modes. Instant mode displays an animation of a series of earthquake instances taking place in different geographical locations globally over time. Aggregate mode displays the aggregate level of instances of the earthquakes over time. Analysis mode provides a yearly graphical information along with some basic statistics for the user's further analysis. Selected area mode extends the analysis mode by allowing the user to look through the world map and examine different geographical areas as the EQviz provides basic statistics such as the average and standard deviation values of the earthquake magnitudes along with the graphical information of the selected area.